Investigation into the Usability of the Maackia amurensis Lectin in Bacterial Diagnosis with the Help of Transmission Electron Microscope - Yosun Mater (European Journal of Biology)
Objective: Glycoconjugates are known to play a crucial role in the attachment-recognition relationship of prokaryotic cells, particularly bacteria. Therefore, understanding the function and properties of these glycoconjugates is of great importance.Materials and Methods: While various methods have provided significant information in determining the chemical structures and functions of sialic acids, histological methods have remained essential in determining their function and location in living organisms. The discovery of lectins with unique marking ability based on the bond structures of sialic acids and the development of antibodies, which can be microscopically distinguished by adding colloidal silver and gold particles, were significant milestones. In the 1990s, methods were developed to specifically mark the types and locations of sialic acids using immunocytological, histological, and fluorescence microscopy methods with fluorescently labeled lectins and antibodies. These methods still remain valid and important today. Using this information, it is possible to create smart drugs and biomarkers specific to bacteria.Results: In this study, the unique connections of gold-labeled lectins with different bacteria were demonstrated with the help of transmission electron microscopy.Conclusion: Our study supports the idea that labeled lectins could be used for rapid and precise bacterial diagnosis.